Adult mouse basal forebrain harbors two distinct cholinergic populations defined by their electrophysiology - Unal, Cagri T.; Golowasch, Jorge P.; Zaborszky, Laszlo (Frontiers in Behavioral Neuroscience, 2012)
We performed whole-cell recordings from basal forebrain cholinergic neurons in transgenic mice expressing enhanced green fluorescent protein under the control of choline acetyltransferase promoter. Basal forebrain cholinergic neurons can be differentiated into two electrophysiologically identifiable subtypes: early and late firing neurons. Early firing neurons (70%) are more excitable, show prominent spike frequency adaptation and more susceptible to depolarization blockade, a phenomenon characterized by complete silencing of the neuron following initial action potentials. Late firing neurons (30%), albeit being less excitable, could maintain a tonic discharge at low frequencies. In voltage clamp analysis, we have shown that early firing neurons have a higher density of low voltage activated calcium currents. These two cholinergic cell populations might be involved in distinct functions: the early firing group being more suitable for phasic changes in cortical acetylcholine release associated with attention while the late firing neurons could support general arousal by maintaining tonic acetylcholine level.